THE IMPLEMENTATION OF RESPONSIBILITY CHARACTER AND INTEGRATED DISCIPLINE VALUES IN INTEGRATED THEMATIC LEARNING AT ELEMENTARY SCHOOL - Sumiati Sumiati (Universitas Tanjungpura, 2021)
Abstract This study aims to describe the inculcation of the character of responsibility and discipline that is integrated into integrated thematic learning in 46 Elementary Schools in Singkawang City. This research is a descriptive study with a qualitative approach. The subjects of this study were school principals, teachers and students at SD Negeri 46 Singkawang City. The data was collected by observing, interviewing and documenting. Data analysis was carried out in stages: data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses triangulation techniques and triangulation of data sources. The results showed that the inculcation of the values of responsibility and discipline that were integrated into integrated thematic learning was as follows: (1) The planning that the teacher has includes the character of responsibility and discipline in schools. The character of responsibility and discipline is explicitly stated in the RPP. (2) In practice, students have carried out the responsibility and discipline properly. (3). Evaluate the results by assessing the character of responsibility, discipline and cooperation in the learning process. (4) The constraints faced are the school community and the community around the school environment do not have full awareness of responsibility and discipline towards predetermined rules. Keywords: Cultivating Character Value, Responsibility, Discipline, Integrated Thematic Learning.